2016
DOI: 10.1097/hjh.0000000000000809
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade albuminuria and incidence of cardiovascular disease and all-cause mortality in nondiabetic and normotensive individuals

Abstract: In apparently healthy individuals with optimal blood pressure and no diabetes, LGA independently predicts CVD incidence and all-cause death, particularly with the large contribution to the excessive incidence of CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 47 publications
(60 reference statements)
5
52
0
1
Order By: Relevance
“…Recently, many researchers have focused on the clinical effects of low-grade albuminuria, which is defined as high level within urinary albumin-to-creatinine ratio (UACR) < 30 mg/g (10)(11)(12)(13)(14)(15)(16). Previous studies have shown an association between a high UACR and various cardiometabolic risk factors (10)(11)(12)(13)(14)(15)(16). In addition, some factors, including various cardiometabolic risk factors, have been shown to predict a high UACR; additional studies investigating new markers of a high UACR are on-going.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have focused on the clinical effects of low-grade albuminuria, which is defined as high level within urinary albumin-to-creatinine ratio (UACR) < 30 mg/g (10)(11)(12)(13)(14)(15)(16). Previous studies have shown an association between a high UACR and various cardiometabolic risk factors (10)(11)(12)(13)(14)(15)(16). In addition, some factors, including various cardiometabolic risk factors, have been shown to predict a high UACR; additional studies investigating new markers of a high UACR are on-going.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown that low-grade albuminuria, defined as UACR as 0 to 30 mg/g, an earlier stage with UACR below the microalbuminuria threshold, is also associated with an increased risk of incident cardiovascular disease and all-cause mortality101112. The Heart Outcomes Prevention Evaluation (HOPE) study found a continuous association between levels of UACR and cardiovascular events6.…”
mentioning
confidence: 99%
“…Current data interpret MAU as a reliable marker of renal dysfunction and as a manifestation of total microvascular lesion and general cardiovascular risk [11]. Research of 1-2 degree hypertension showed that MAU rate in these patients is 12-22%, but the combination with obesity increases it to 30-40% [12].…”
Section: Fundingmentioning
confidence: 99%